(untitled) (Móin-Móin - Revista de Estudios sobre Teatro de Formas Animadas, 2018)
In the spring of 2006, Great Small Works was commissioned by the Lower Manhattan Cultural Council to make an art parade to kick off the River to River Festival, a summer-long series of concerts and performances whose goal, it seems to me, was to bring back a sense of lively public culture to the still-traumatized environs of 2001’s “Ground Zero.” While previous years’ parades had been collections of New York City artists’ processional sculptures, we decided to make our River to River parade a street theater event, a politically themed meditation on rivers, streets, and the dynamics of power in communities faced with transformation and change. In this, of course, we were following the kinds of traditions which Bread and Puppet Theater, Welfare State International, and other groups in the seventies had pursued; as well as the rich processional traditions of the 1920s and 30s; centuries of outrageous carnival street performance, Renaissance outdoor spectacle; and even the origins of Greek tragedy in the wheel-mounted processional boats – the carre navalis – which some have considered the roots of European carnival.